Prevalencia de hemotrópicos en equinos (Equus caballus, Equus asinus e híbridos) del cantón Chone - Menéndez Bravo, José Luis (2024)
Hemoparasites affect animals that live in tropical and subtropical areas, being transmitted by vectors such as ticks, blood-sucking flies and other mechanical factors. In this group of diseases, Trypanosomosis and Babesiosis stand out as having significant negative impacts on production, economy and public health, an accurate diagnosis plays a fundamental role in the control and sustainable treatment of these conditions. On the Ecuadorian coast, these diseases have been barely investigated. Therefore, the objective of this study was to determine the prevalence of hemotropic drugs in farms and stables located in Balzar, Colorado, Danda and the city of Chone, province of Manabí. Specific parasitological diagnoses were made for babesiosis using blood smears and for Trypanosomosis using the Woo method. The results revealed a prevalence of 0% for both diseases in the production units studied, thus ruling out the possible circulation of these hemoparasites and the associated risk factors during the research period. Although the animals studied did not present clinical signs, it cannot be ruled out that these hemoparasites represent a silent threat. Therefore, the implementation of comprehensive vector control programs is suggested to improve good agricultural practices related to the species studied.